Engenharia, docência e discência: narrativas sobre avaliação - Matta, Eduardo Nadaleto da (2021)
The 21st century teacher is no longer the one who teaches, but a professional who must be in constant search for resources to intermediate learning and awaken the interest of his or her students. 21st century education is not like that of the last century due to the cultural changes the world has gone through and is dedicated to learning and not to teaching. Notably, the pedagogy adopted in Engineering courses is inadequate for students' learning. Based on these considerations, the problem of this research is: "Considering that the students of an Engineering course come to the university with new and differentiated educational experiences, should we continue to assess them as they were assessed in the traditional teaching system?". For this study, narrative research was used with the aim of investigating, from the perspective of the teacher and the student, in their narratives, some ideas about the current assessment process of an Institution of Higher Education in the region of the great ABC Paulista. As pointed out by Clandinin and Connelly (2011), the narrative research should be understood to understand the human experience, since it studies stories lived and told, based on the reconstruction of social events from the point of view of the interviewee, being the purpose of the interview to collect and listen, in its uniqueness, the speech of a person at a specific moment of their existence and their experience. From the interviews, it was noted the need for the development of an assessment process that overcomes the classificatory and authoritarian assessment model, turning it into a learning instrument. The assessment, which should have a diagnostic function to help each student in his process of growth towards autonomy, should be concerned with the process of appropriation of knowledge by the student, mediated by the active intervention of the teacher. According to Anastasiou and Alves (2007), the assessment, usually centered on the teacher and performed at the end of the subjects, needs to be centered on the student and on learning as an integrated part of the curriculum, removing the student from the passive role, reinforcing the formative role of assessment. In their works, Luckesi and Chaves (2000, 2001) recalled that the act of assessment implies the willingness to accept and release, being an important tool available to teachers to achieve the main goal of the school: to make students evolve. Thus, the improvement in the teaching-learning process depends on a restructuring, especially with regard to assessment, as well as the development of new skills by the teaching staff. Based on the sensitive listening of teachers and students and on the challenges of Engineering for the 21st century, which impose necessary changes in the formation of engineers, this work proposes a teacher training track in assessment, which seeks to transform assessment into a learning tool and, at the same time, into a tool for reflection and awareness of the development about the teaching and learning process.